Al-Shāṭibīs sufismekritik: Hvorfor en ʿālim fra al-Andalus forkastede askese og virtuosereligiositet - Riexinger, Martin (Religionsvidenskabeligt Tidsskrift, 2016)
The faqīh (Islamic legal scholar) al-Shāṭibī (d. 1388) from Granada is primarily known for his innovative approach within the field of legal theory (uṣūl al-fiqh). However, he dedicated much attention to the criticism of sufism. But like other Islamic scholars who opposed Sufism he did not primarily attack infringements on the ‘rights of God’. Instead he highlighted that the ascetic practices propagated by the Sufis are detrimental to the welfare of both the individual Muslim and society as a whole. Furthermore he argues that their charismatic authority based on their asceticism and miracles allegedly bestowed on them threatens to undermine Islamic jurisprudence (fiqh) along rational and intersubjective lines.